Interaksi Mamak dan Kamanakan Sebagai Sumber Penciptaan Karya Tari Buek Arek Karang Taguah - Cufara, Dwindy Putri; Oktavianus, Oktavianus; Gusmanto, Rico (Universitas Hamzanwadi, 2021)
The social phenomenon between mamak and kamanakan in Minangkabau is the source of the creation of the dance title Buek Arek Karang Taguah. Looking at the current phenomenon, there is a dissociative interaction that causes the waning of tolerance and harmony between mamak and kamanakan. The purpose of the creation of this art is to create a work of dance art originating from the phenomenon between mamak and kamanakan which is viewed from social values and to reveal the condition of closeness between mamak and kamankan which has been reduced through dance movements. This work is done using a literary theme which is actualized in three ideas, namely; (1) expressing the relationship between mamak and kamanakan as indak bapamatang fields, (2) expressions of dissociative interactions as the cause of the breakdown of tolerance and harmony between mamak and kamanakan, (3) expressions of the relationship between mamak and kamanakan that should be in the value of cooperation. The manufacturing methods used include research, concept surgery, exploration, movement arrangement, and evaluation. The creation of this work provides knowledge about the importance of harmony between mamak and kamanakan.Â